Evaluation of OralScreenKKU Prototype Application in Elderly - Sutanchaiyanonta, Wilaiporn; Patcharanuchat, Piyachat; Srimongkol, Kanyarut; Somorn, Chanida; Leelapakorn, Thapanee (Khon Kaen University Dental Journal, 2023)
This research is an evaluative study aimed at assessing the overall quality of the prototype application OralScreenKKU. The researchers studied theories related to app assessment and made improvements to develop an app evaluation questionnaire for self-administered responses. Data was then collected from individuals aged 60 years and above, selected conveniently among those receiving dental services at the Faculty of Dentistry, Khon Kaen University Hospital. The collected data was analyzed using statistical methods. The study included a sample group of 35 participants, with 57.1% being female. The average age was 67.5 years, and 77.1% had completed undergraduate or higher education. On average, they used smartphones for 1-3 hours per day, with 48.6% using LINE, YouTube, and Facebook as the most frequently used applications, at 97.1%, 60.0%, and 51.4%, respectively. The app assessment consisted of 16 questions, with a maximum score of 1. The study found that the app demonstrated very high-quality content and usability, with an average score of 0.80±0.40, as well as high-quality design (0.74±0.44). The first issues to address were screen freezing and difficulty accessing certain menus. The findings can be used to make improvements to the app before its public release, and further research should be conducted in the future. It is advisable to increase the diversity and number of sample groups to achieve the objectives of developing the OralScreenKKU prototype app, which aims to be a useful tool for self-screening oral health conditions.